"WAIT AND SEE" OR "FEAR OF FLOATING"?. (7th June 2022) - Lei, Xiaowen; Lu, Dong; Kasa, Kenneth
Abstract : This paper studies the evolution of China's exchange rate policy using real options theory. With intervention costs and ongoing uncertainty, intervention involves the exercise of an option. Increased uncertainty increases the value of this option. This "wait and see" effect leads the Central Bank to widen its intervention band. However, increased volatility also produces larger fluctuations in welfare, which creates a "fear of floating." This induces the Central Bank to set a tighter band. To study this trade-off, our paper incorporates stochastic volatility into a new Keynesian target zone model and then calibrates it to data from China. We find that increased uncertainty leads to a tighter intervention band, both in the data and in the model. Hence, in China, "fear of floating" appears to dominate the "wait and see" effect.